Determinants of household food security during the COVID-19 pandemic in Tulungagung, East Java - Novianti Tysmala Dewi; Dwi Nastiti Iswarawanti; Novi Sylvia Hardiany (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2023)
Food insecurity remains a significant problem in Indonesia, with severe levels of hunger, due to inadequate food consumption and poor quality. Since the COVID-19 pandemic, changes in the food system and possible income losses have threatened household food security in Indonesia. This study aims to assess the determinants of household food security during the COVID-19 pandemic. This descriptive-analytic research method with a cross-sectional study was conducted from May to July 2021. The sampling technique used random sampling to obtain two villages with 187 parents in Tulungagung, East Java. Data collection on sociodemographic characteristics, social assistance, the impact of COVID-19, coping strategies, and household food security used interview techniques via WhatsApp and telephone. Testing in this study used chi-square for bivariate analysis and multiple logistic Regression for multivariate analysis. The results showed that the prevalence of food insecurity in Tulungagung was 56,1%. After adjusting for several potential confounding factors, such as income (p= 0,021; OR= 2,388), type of social assistance (NGO) (p= 0,002; OR= 3,945), change in employment status (p= 0,044; OR= 2,026), and food compromise coping strategy (p= 0,008; OR= 10,134) are determinants of household food security. In conclusion, the determinants of household food security are income, change in employment status, type of social assistance (NGO), and food compromise coping strategies.